THE IMPACT OF THE INDUSTRIAL CULTURAL LANDSCAPE CONVERSION THROUGH TOURISM ON THE ENVIRONMENTAL ELEMENTS OF OCNA MUREȘ - VASILIȚĂ-CRĂCIUN, Ileana-Cristina (Studia Universitatis Babeș-Bolyai Geographia, 2021)
The fulminant technological advance, corroborated with the increasing demand of products have favored, in the recent period, the accentuation of the various processes of environmental pollution, with particularly serious consequences on the living organisms. Thus, the European Green Pact is the instrument through which the European Union wants to establish the necessary steps to reduce air, water and soil pollution (by 2050), as the main elements of the environment affected by pollution. It is therefore recommended that the quality standards provided by the international forums be respected and that the specific legislation of all member states be aligned for a unified approach. In this regard, the implementation of the clean industrial technologies, recycling, the use of green energy in the production process, the use of natural resources in a sustainable manner or the conversion of industrial elements into tourism elements, can be viable means to achieve the goals proposed in the pact. In the context of those presented, this study seeks to argue the conversion of the industrial cultural landscape related to the exploitation and processing of local salt resources and the specific hazards, found at Ocna Mureș (Alba County), in the cultural and tourist-validated landscapes. The change of the function of the mentioned elements can favour the socio-economic revival of the area, with the observance of the new European environmental norms, in the medium and long term.